The transcription factor Hhex regulates inflammation-related genes in microglia - Risa Sakate; Masahiro Nishiyama; Yu Fukuda; Shiho Kitaoka; Tomoyuki Furuyashiki (Elsevier, 2022)
Microglia have diverse physiological and pathological functions. However, the transcriptional mechanisms remain elusive. Here we sought new transcription factors relevant to microglial functions from the microglial transcriptome of stressed mice and evaluated their roles in primary microglia. TLR2 and TLR4 agonists increased Rel, Atf3, and Cebpb and decreased Hhex in primary microglia as repeated social defeat stress. Although Hhex was not studied in microglia, TLR2 and TLR4 agonists decreased Hhex, and Hhex overexpression attenuated TLR4-increased expression of inflammation-related genes. These findings suggest that Hhex negatively regulates inflammation-related genes in microglia and that TLR2/4 activation reduces Hhex, facilitating TLR4-mediated neuroinflammation.